Imobilização de papaína em membranas de nanocelulose bacteriana - Petersohn Junior, Egon (2019)
Bacterial nanocellulose is a type of cellulose produced in the form of a hydrogel membrane by some bacteria and has unique properties such as high purity and crystallinity, high water retention capacity (> 98%), mechanical strength, threedimensional structure of fibrils of cellulose at nanometric scale and biocompatibility. Papain is a plant protease of wide commercial use, mainly in the food, cosmetic and medical industry. The study aimed to produce and use bacterial nanocelulose membrane to immobilize papain using two methods - adsorption and crosslinking - to evaluate the biopolymer as the proteolytic activity under different reaction conditions and its reuse. Bacterial nanocellulose membranes were produced by static culture of Gluconacetobacter sp. After 5-7 days of culturing at 28 °C membranes were produced in a yield of 5.3 g/L of culture medium (dry weight). The best pH range for immobilization by both techniques was close to neutral. The optimum azocasein hydrolysis temperature in the two forms of immobilized papain was between 70-80 °C, with an optimum pH of activity being 7.0. Regarding the stability after 2 h incubation at different pHs, free papain presented higher stability at pHs 3, 7, and 11 than the forms immobilized on the bacterial nanocellulose membrane. Already considering stability to high temperatures, after incubation at 75 °C for 2 h, papain immobilized by the adsorption method presented 81% residual activity against only 43% residual free form activity. Regarding the residual relative activity measured after 4 hours of preincubation in different organic solvents, papain immobilized by adsorption presented high stability against ethanol (96.4% of residual relative activity against 85.6% of free papain) whereas papain immobilized by crosslinking had a higher stability to dimethylsulfoxide (35.2% residual activity versus 0.5% free papain). Compared to hexane, the two immobilized forms of papain showed equivalent residual activities (92.3% for the two forms versus 83.7% of the free form). Incubation for 1 h with bivalent metals (20 mM) showed residual activity 13.4% and 29.5% relative to copper and 16.2% and 34.2% for zinc in the immobilized forms of papain by adsorption and crosslinking , respectively. After seven cycles of reuse the papain immobilized by crosslinking presented 53.5% of its original activity and 31.6% for the immobilized by adsorption. Storage at 28 °C in dry form of immobilized form by crosslinking allowed the maintenance of 100% of its proteolytic activity, while the immobilized by adsorption had 80% of its preserved activity after 4 weeks. The results show that it is possible to add new characteristics to both the enzyme and the nanocellulose itself, with the possibility of application as curatives with debriding action.